Tingkat enjoyment peserta didik sekolah dasar terhadap physical activity break dalam pembelajaran - ismail gani; Yudanto; Hendra Setyawan; Willy Ihsan Rizkyanto (Universitas Sarjanawiyata Tamansiswa, 2023)
The duration of learning activities is an external factor that needs to be considered in the learning process in lower-grade elementary schools. Physical Activity Break, translated as rest with physical activity, is an alternative activity to solve the problem of learning duration and long sitting time for elementary school students. This study aims to determine the level of enjoyment of lower-grade elementary school students in Yogyakarta on implementing Physical Activity Breaks in the learning process. This study uses a quantitative descriptive method. The sample in this study used a simple random sampling technique. Sample data from the total population of SD Masjid Syuhada students in the DIY area. The sample in this study was taken as many as 64 students. The instrument used is a questionnaire with 12 statement items; experts have been consulted and tested valid and reliable. Data analysis techniques in this study were carried out using descriptive statistical tests with the help of SPSS software. The results of the analysis in this study are presented in the form of minimum (Min), Maximum (Max), Mean (M), Median (Me), Mode (Mo), Standard Deviation (SD), Frequency Distribution, Histogram, and Percentage per aspect and item. Based on the study's results, it has been shown that the frequency of the Enjoyment Level of Elementary School students for Physical Activity Breaks is at most 30 (46.9%) at intervals of 11-12. At the same time, there are at least two students (00%) at intervals 13-14 and 15-16. Furthermore, the total score for the Enjoyment Level for PAB is 650, and the criterion score for the Enjoyment Level for PAB is 768, so the percentage value reaching 84.64 is in the very high category. Thus it can be concluded that elementary school students' enjoyment of physical activity breaks in learning can be very high based on the quantitative research results. The feelings of pleasure and comfort experienced by students, as well as the positive impact of implementing Physical Activity Breaks, are the key to successful learning in schools.